The feasibility of vagal nerve stimulation revision surgery and surgical techniques: a retrospective review. (1st July 2021) - Al Omari, Ahmad I.; Nuseir, Amjad; Kanaan, Yazan; Al-Ashqar, Ra'ed; Alzoubi, Firas
Abstract: Background: With the large number of VNS implants performed worldwide, the need for removal or replacement of the device in selected cases is emerging, this removal or replacement of VNS can be challenging. Aims/objective: To describe the feasibility and safety of revising vagal nerve stimulation surgery in terms of the indications, surgical techniques, and outcomes. Materials and methods: A retrospective study, a series of eight cases with VNS implants that needed revision surgery have been reviewed, four devices were completely removed and four were only revised. The revision surgery was performed after a range of 7 months to 6 years, due to different reasons. Initial surgeries and revisions were performed at the otolaryngology department in a major tertiary center. Conclusions and significance: We concluded that the previously implanted vagal nerve stimulation electrodes can be completely removed without any significant sequelae on the nerve. It may also be re-implanted safely at the previously used segment of the vagus nerve with a similar outcome in seizure control as the initial implantation.